Design and Synthesis of Novel 5-((3-(Trifluoromethyl)piperidin-1-yl)sulfonyl)indoline-2,3-dione Derivatives as Promising Antiviral Agents: In Vitro, In Silico, and Structure-Activity Relationship Studies - Rogy R. Ezz Eldin; Marwa A. Saleh; Sefat A. Alwarsh; Areej Rushdi; Azza Ali Althoqapy; Hoda S. El Saeed; Ayman Abo Elmaaty (MDPI AG, 2023)
Herein, a series of new isatin derivatives was designed and synthesized (1-9) as broad-spectrum antiviral agents. Consequently, the antiviral activities of the synthesized compounds (1-9) were pursued against three viruses, namely influenza virus (H1N1), herpes simplex virus 1 (HSV-1), and coxsackievirus B3 (COX-B3). In particular, compounds 9, 5, and 4 displayed the highest antiviral activity against H1N1, HSV-1, and COX-B3 with IC50 values of 0.0027, 0.0022, and 0.0092 µM, respectively. Compound 7 was the safest, with a CC50 value of 315,578.68 µM. Moreover, a quantitative PCR (real-time PCR) assay was carried out for the most relevant compounds. The selected compounds exhibited a decrease in viral gene expression. Additionally, the conducted in silico studies emphasized the binding affinities of the synthesized compounds and their reliable pharmacokinetic properties as well. Finally, a structure-antiviral activity relationship study was conducted to anticipate the antiviral activity change upon future structural modification.